PS 07-27 ANTI-FIBROTIC EFFECTS OF AT2 RECEPTOR AND MAS RECEPTOR STIMULATION IN STROKE-PRONE SPONTANEOUSLY HYPERTENSIVE RATS. (September 2016) - Widdop, Robert; Baraldi, Dhaniel; Wang, Yan; Jones, Emma; Gaspari, Tracey
Abstract : Objective: Angiotensin II type II receptor (AT2 R) and the Mas receptor (MasR) belong to the 'protective arm' of the RAS. Either AT2 R or MasR stimulation is known to evoke a number of cardiovascular effects, including acute vasodilatation as well as chronic anti-fibrotic effects. Compound 21 (C21) is the prototypical AT2 R agonist, while Ang (1–7) has mainly been used in chronic studies to stimulate MasR, although this heptapeptide is relatively nonselective. Therefore, we examined if selective AT2 R (using C21) or MasR (using AVE0991) stimulation would evoke similar anti-fibrotic phenotypes to that of combination treatment, which may implicate similar signalling mechanisms. Design and Method: To investigate if AT2 R and MasR pharmacological co-stimulation would provide additional protection against end-organ damage in stroke-prone spontaneously hypertensive rats (SP-SHR) than either treatment alone. Adult male SP-SHR, aged 20–22 weeks, were treated for 4 weeks with either saline (n = 7), AT2 R agonist C21 (0.03 mg/kg/day, n = 6), MasR agonist AVE0991 (24 μg/kg/h, n = 3), or a combination of both (n = 4), subcutaneously via osmotic mini-pump. Blood pressure (tail-cuff) was measured at days 0, 14 and 28 of the protocol. At the end of treatment, indices of aberrant cardiac remodeling (cardiac hypertrophy and interstitial fibrosis) were quantified. Results: None of the treatments influenced elevated blood pressure or cardiac hypertrophy in SP-SHR. However, cardiac interstitial fibrosis (assessed by picrosirius red staining) was strikingly attenuated from control levels (collagen volume fraction 5.5%) to approximately half those levels by each treatment (2.6%, 2.7% for C21 and AVE0991, respectively, both P < 0.01 versus untreated) while there was no additive anti-fibrotic effect of combination treatment (collagen volume fraction 2.4%). Conclusions: Pharmacological stimulation of AT2 R and/or MasR exhibited marked cardiac anti-fibrotic effects without influencing blood pressure. Ongoing studies will address whether or not similar mechanisms contribute to altered extracellular matrix.